Implementasi Metode Pictorial Representation untuk Mengurangi Konsumsi Gula, Garam dan Lemak sebagai Upaya Mewujudkan Generasi Sehat Indonesia Unggul - Meinarisa, Meinarisa; Nasution, Riska Amalya; Mawarti, Indah; Yuliana, Yuliana; Martawinarti, RTS Netisa (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service aims to help elementary school children to know and measure the amount of sugar, salt, and fat (GGL) consumption through the implementation of the Pictorial Representation method as an effort to create a healthy generation and a superior Indonesia. Community service activities were carried out at the elementary school level because elementary school-aged children are in a period of growth that requires sufficient nutritional intake. The method of implementing this service used counseling and demonstration. Participants involved in this activity amounted to 50 people from grades 3, 4, and 5 of SDN 61 Talang Babat, Jambi Province. Evaluation of activities was carried out using a questionnaire and analyzed descriptively. The results of this community service showed that there was an increase in knowledge in students and they were able to measure GGL and healthy food consumption every day. In addition, students could understand well about the types of food and food groups. The implications of this activity are expected to be continued by teachers, especially those on duty in the UKS.